Human Behaviour in Design 2003
DOI: 10.1007/978-3-662-07811-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Strategic knowledge differences between an expert and a novice designer

Abstract: Abstract. This chapter investigates the differences in performance between an expert and a novice in terms of their respective strategic knowledge. We examined conceptual design protocols of an expert and a novice, and found that the expert's cognitive activity and productivity in the design process were almost three times as high as the novice's. The possible reason for this is the difference in their strategic knowledge. The expert's cognitive processing is structured such that it stays within the limits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 8 publications
2
15
0
2
Order By: Relevance
“…Through the sketching activities, it have evoked the students to the unexpected discoveries (Schon & Wiggins, 1992), triggered new meanings (Goldschmidt, 1991), and illustrated the ability to transform and generate new images in mind while sketching (Kavakli & Gero, 2001;Kavakli, Suwa, Gero, & Purcell, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the sketching activities, it have evoked the students to the unexpected discoveries (Schon & Wiggins, 1992), triggered new meanings (Goldschmidt, 1991), and illustrated the ability to transform and generate new images in mind while sketching (Kavakli & Gero, 2001;Kavakli, Suwa, Gero, & Purcell, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some claimed students have weakness in the ability of sketching (Kavakli & Gero, 2001), generated lower number of sketches and interpretations (Purcell & Gero, 1998), and have limited access to knowledge that resulted in failure to recognise problems and reflect on the previous projects (Ahmed et al, 2003;Lawson, 2004). However, (Higgins et al, 2009) believed that the most important value of studio learning is locates at its Socratic method of open inquiry and active learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A whole body of works focuses on, and reflects over, the difficulties of teaching and learning the design activity, taking into account the advancements in the fields of cognitive sciences, sociology and education ( [2,[6][7][8]). …”
Section: Related Workmentioning
confidence: 99%
“…Thus, novice designers would find difficulties in designing intuitively if experience and knowledge are not sufficiently gained. Subsequently, further research works have been explored on how knowledge and experience were used among experienced and novice designers such as in [2,3] and [4]. Reference [4] suggested that design strategies, knowledge, and information should be included in developing support methods for novice designers as a guide to them.…”
Section: Introductionmentioning
confidence: 99%